Cingulate Alpha-2A Adrenoceptors Mediate the Effects of Clonidine on Spontaneous Pain Induced by Peripheral Nerve Injury - Wang, Yong-Jie; Zuo, Zhen-Xing; Wu, Cheng; Liu, Li; Feng, Zhi-Hui; Li, Xiang-Yao (Frontiers in Molecular Neuroscience, 2017)
The anterior cingulate cortex (ACC) is an important brain area for the regulation of neuropathic pain. The α2A adrenoceptor is a good target for pain management. However, the role of cingulate α2A adrenoceptors in the regulation of neuropathic pain has been less studied. In this study, we investigated the involvement of cingulate α2A adrenoceptors in the regulation of neuropathic pain at different time points after peripheral nerve injury in mice. The application of clonidine, either systemically (0.5mg/kg intraperitoneally) or specifically to the ACC, increased paw withdrawal thresholds (PWTs) and induced conditioned place preference (CPP) at day 7 after nerve injury, suggesting that cingulate α2 adrenoceptors are involved in the regulation of pain-like behaviors. Quantitative real-time PCR data showed that α2A adrenoceptors are the dominant α2 adrenoceptors in the ACC. Furthermore, the expression of cingulate α2A adrenoceptors was increased at day 3 and day 7 after nerve injury, but decreased at day 14, while no change was detected in the concentration of adrenaline or noradrenaline. BRL-44408 maleate, a selective antagonist of α2A adrenoceptors, was microinfused into the ACC. This blocking of cingulate α2A adrenoceptors activity abolished the CPP induced by clonidine (0.5mg/kg intraperitoneally) but not the effects on PWTs at day 7. However, clonidine applied systemically or specifically to the ACC at day 14 increased the PWTs but failed to induce CPP; this negative effect was reversed by the overexpression of cingulate α2A adrenoceptors. These results suggest that cingulate α2A adrenoceptors are necessary for the analgesic effects of clonidine on spontaneous pain.